The effectiveness of direct school funding approach in primary schools in Tanzania: A case of Chalinze District - Gamba, Charles (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for the award of Master of Arts in Education (MAED) degree of Mzumbe University